Observation the Multi-Soliton Patterns From the Er-Doped Mode-Locked Fiber Laser Modulated by PtSe2 - Wu, Man; Jiang, Guobao (Frontiers in Physics, 2020)
The passively mode-locked fiber laser can provide an ideal platform to investigate the soliton dynamics for it can be modeled by the complex Ginzburg-Landau equation well. Here, we experimentally studied the formation and dynamics of soliton patterns in an erbium-doped fiber laser mode-locked by PtSe2 based saturable absorber via evanescent field interaction. With the increase of pump power, different soliton patterns, such as single soliton, two solitons and bound soliton, can be observed experimentally. The results can identify the nonlinear optical response of the PtSe2, and may make way for unveiling the nature of the soliton dynamics in the fiber laser system.